The Influence of Communication, Ability, and Work Experience on Employee Performance at Bank BRI Rantauprapat Branch - Solihin Lubis; Siti Lam’ah Nasution; Bhakti Helvi Rambe (Budapest International Research and Critics University, 2022)
This study aims to analyzecommunication, ability, and work experience on employee performance at Bank BRI Rantauprapat Branch. This study uses quantitative methods with several tests namely classical assumption test, multiple linear regression, hypothesis testing and R2 test. Partially, the value of the communication variable (X1) has a tcount of 4.53. When compared with t table, the results are 4.53> 1.68, so it can be concluded that the communication variable (X1) has a positive and significant effect on the employee performance variable (Y). The ability variable (X2) has a tcount of 3.84 and when compared with ttable, the result is 3.84 > 1.68, so it can be concluded that the ability variable (X2) has a positive and significant effect on the employee performance variable (Y). The work experience variable (X3) has a tcount of 6, 65 and when compared with t table, the result is 6.65 > 1.68, so it can be concluded that the work experience variable (X3) has a positive and significant effect on the employee performance variable (Y). Simultaneously, the variables of communication, ability, and work experience have a positive and significant influence on employee performance, meaning that the hypothesis in this study is accepted, as evidenced by the value of Fcount > Ftable (30.32>2.83).